Supplementation of organic acid blends in water improves growth, meat yield, dressing parameters and bone development of broilers - Hossain, ME; Nargis, F (Bangladesh Journal of Animal Science, 2016)
The present study was conducted in order to examine the effects of supplementing two liquid organic acid blends on growth performance, meat yield, dressing parameters, organ weights and bone development of broilers. A total of 120 broiler chicks were assigned to five dietary treatments in four replications with six birds per replication over a period of 5 weeks, following a completely randomized design. Dietary groups included; Control = Without organic acids; AW-C = Activate continuous administration; AW-P = Activate periodic administration; N-C = Nutrilac continuous administration; N-P = Nutrilac periodic administration. Results indicated that supplementation of organic acids improved (P<0.05) growth performance of broilers compared to the control. Among the supplemented groups, highest (P<0.05) body weight and body weight gain were in the AW-C group, followed by the N-C, AW-P, and N-P groups. Feed intake was higher (P<0.05) in the AW-C and N-C groups compared to the N-P and control groups. Feed conversion ratio was improved (P<0.05) in the organic acid groups, and the AW-C group showed the best value. Dressing yield as well as thigh and drumstick meat relative weights were higher (P<0.05) in the organic acid groups compared to control, whereas breast meat increased (P<0.05) in the AW-C group compared to the AW-P and control groups. Increased (P<0.05) relative weights of head and neck were observed in the AW-C group as well as that of gizzard in the N-C group compared to the other groups. On the other hand, abdominal fat content decreased (P<0.05) in the organic acid groups. Whole leg and wing bone relative weights increased (P<0.05) in the AW-C, AW-P, and N-C groups compared to the other groups. Further, longer (P<0.05) shank in the organic acid groups as well as longer drumstick bone length in the AW-C group were observed compared to the other groups. It was concluded based on the study results that supplementation of both organic acid blends improves growth performance, increases meat yield, organ development, dressing parameters and influences bone development of broilers. Therefore, as continuous addition of Activate showed better results compared to Nutrilac in terms of some tested parameters, it could be applied to broiler water to exert beneficial effects. Bang. J. Anim. Sci. 2016. 45 (1): 7-18